FAD-deficient P187S mutation of NAD(P)H:quinone oxidoreductase 1 (NQO1*2) binds and accelerates β-amyloid aggregation. Issue 11 (14th November 2022) - Panja, Sudipta; Siegel, David; Camandola, Simonetta; de Cabo, Rafael; Ross, David; Mallela, Krishna M.G.
Abstract: Alzheimer's disease (AD) is one of the most prominent neurodegenerative diseases. Results from animal and cellular models suggest that FAD-deficient forms of NAD(P)H quinone oxidoreductase 1 (NQO1) may accelerate the aggregation of Alzheimer's amyloid-β peptide (Aβ1-42 ). Here, we examined in vitro whether NQO1 and its FAD-deficient P187S mutation (NQO1*2) directly interact with Aβ1-42 and modify its rate of aggregation. When monitored using the fluorescence of either noncovalent thioflavin T (ThT) or HiLyte Fluor 647 (HF647) dye covalently attached to the Aβ1-42 peptide, the aggregation kinetics of Aβ1-42 were markedly more rapid in the presence of NQO1*2 than the wild-type (WT) NQO1. Experiments using apo-NQO1 indicate that this increase is linked to the inability of NQO1*2 to bind to FAD. Furthermore, dicoumarol, an NQO1 inhibitor that binds near the FAD-binding site and stabilizes NQO1*2, markedly decreased the aggregation kinetics of Aβ1-42 . Imaging flow cytometry confirmed in-vitro coaggregation of NQO1 isoforms and Aβ1-42 . Aβ1-42 alone forms rod-shaped fibril structures while in the presence of NQO1 isoforms, Aβ1-42 is incorporated in the middle of larger globular protein aggregates surrounded by NQO1 molecules. Isothermal titration calorimetry (ITC) analysis indicates that Aβ1-42 interacts with NQO1 isoforms with a specific stoichiometry through a hydrophobic interaction with positive enthalpy and entropy changes. These data define the kinetics, mechanism, and shape of coaggregates of Aβ1-42 and NQO1 isoforms and the potential relevance of FAD-deficient forms of NQO1 for amyloid aggregation diseases.